Retinoid-induced Histone Deacetylation Inhibits Telomerase Activity in Estrogen Receptor-negative Breast Cancer Cells - Phipps, Sharla M.O. (2009)
BACKGROUND: Multiple mechanisms regulate cancer-associated telomerase activity at the level of human telomerase reverse transcriptase (hTERT) transcription which may serve as novel targets for anticancer approaches. MATERIALS AND METHODS: The effects of prolonged all-trans retinoic acid (ATRA) exposure on hTERT regulation in estrogen receptor-negative SK-BR-3 breast cancer cells were examined. RESULTS: ATRA had a profound effect on the morphology and proliferation rate of the SK-BR-3 cells. ATRA also hindered the ability of these cancer cells to grow independently, rendering them more like normal somatic cells. The effect of ATRA on the decrease of telomerase activity was found to be associated with a rapid decrease in histone H3-lysine 9 acetylation (H3-K9-Ac) of the hTERT promoter. Extended-exposure to ATRA in these cells also caused the initiation of a putative compensatory mechanism, counteracting the induced surge in apoptosis. CONCLUSION: A rapid decrease of H3-K9 acetylation at the hTERT promoter could be an important mechanism by which ATRA shuts down telomerase activity and mediates its antitumor effects in estrogen receptor-negative breast cancer cells.